A Study on Potential Strip Shape Control of High‐Strength Steel during Hot Pinch Rolling Process. Issue 1 (8th September 2020) - Kong, Ning; Zhao, Chuan; Cao, Jianguo; Zhang, Qingdong
Abstract : Hot‐rolled high‐strength steel (HSS) strips always present side‐camber after they are cut into subsections along the rolling direction. To deal with the potential strip shape defect of hot‐rolled HSS, the nonlinear finite element (FE) software is applied to establish a 3D model of pinch roll and strips to simulate the pinch rolling process before the hot rolling coiler. The effects of temperature distribution, roll wear, friction coefficient, initial strip flatness defects, and tension on the strip longitudinal extension distribution are studied along the width direction. The results indicate that the pinch roll wear presents a great influence on both the tendency and quantitative value of the strip longitudinal extension distribution. The maximum unevenness value is 178%, and the maximum differences of longitudinal strain between the center and edge of the strips reach to 51.43%. A newly pinch roll contour is proposed to improve the potential strip shape defects. After the industrial application, the average pinch roll wear thickness decreases from 180 to 120 μm. The hot rolled strips are cut into substrips and the maximum side‐camber value decreases from 12 to 3 mm, which meets the requirement from the auto part manufacturers. Abstract : A 3D finite element (FE) model of pinch roll and strips is established to study the potential strip flatness defects of high‐strength steel. The pinch roll contour with variable contact length (PVCR) is proposed and the industrial application indicates a reduction on the maximum side‐camber value.